ARtivismo e resistência: o efeito de visibilidade na cidade do(s) rio(s) invisível(eis) - Giachini, Liana Cristina (2018)
Within this thesis, located in the study field French Discourse Analysis, grounded by Michel Pêcheux and developed in Brazil by Eni Orlandi, we have aimed at understanding the discourse functioning of the urban artistic interventions promoted by the group Coletivo ARtivista Estopô Balaio in Jardim Romano neighborhood, São Paulo City. To do so, we have taken as discursiveness the play “A cidade dos Rios Invisíveis”, by Coletivo ARtivista Estopô Balaio, itinerant spectacle that circulates on the railway lines of Paulista de Trens Metropolitanos (CTPM) Incorporation, through which we have verified the production of the effect of (in)visibility of the subject living in the neighborhood Jardim Romano and the way they mean and are signified in/by urban space. In this gesture of interpretation, we understand the city as a meaningful space, where subjects, social practices, relations between the individual and society acquire material form, as a result of the symbolization of the relation between citizen space and the subjects who inhabit it, who also exist and mean. Our gesture of comprehension took part from the construction of discourse scenes composed by cutouts of the play that build the corpus of the thesis, in which meaning regularities emerge that form nets of repeatability. Our question relies on understanding how the group Coletivo Estopô Balaio moves itself in certain urban narrative, producing meaning effects of presence in the glide of (in)visibility. We highlight, to be short, that, via authorship effect, Coletivo produces in the play an effect of presence of subject-resident in the neighborhood, in the attempt to ensure visibility to such marginal subject. Jardim Romano neighborhood – at the same time scenario and character of the narrative – is constituted as threshold zone: in the space of marginal space, as river and city border, the migrant subject-body, nowadays inhabitant of Jardim Romano signifies by the lack, that is, has its right to the city denied by the absence of material conditions to urban access and (r)exists via Estopô Balaio art.